2017
DOI: 10.1039/c7dt02131c
|View full text |Cite
|
Sign up to set email alerts
|

A mononuclear Co(ii) complex formed from pyridinedimethanol with manifold slow relaxation channels

Abstract: A mononuclear hexacoordinate complex [Co(pydm)](dnbz) formed from 2,6-pyridinedimethanol in the coordination sphere of Co(ii) and dinitrobenzoato anions exhibits magnetic anisotropy of an easy axis type and a field induced slow magnetic relaxation with manifold relaxation channels. The low-frequency relaxation time is as slow as τ = 0.13 s at B = 0.4 T and T = 1.9 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…In a number of cases it was attributed to the same paramagnetic center. 29 And there are few examples of complexes of Co 2+ , [30][31][32][33][34] Ni 2+ , 35 and Cu 2+ , 36 where the slower relaxation path shows weak temperature dependence like in our case. A slow decrease with increasing temperature may even turn back to a weak increase of s at higher temperatures.…”
Section: Relaxation Of Magnetizationmentioning
confidence: 47%
“…In a number of cases it was attributed to the same paramagnetic center. 29 And there are few examples of complexes of Co 2+ , [30][31][32][33][34] Ni 2+ , 35 and Cu 2+ , 36 where the slower relaxation path shows weak temperature dependence like in our case. A slow decrease with increasing temperature may even turn back to a weak increase of s at higher temperatures.…”
Section: Relaxation Of Magnetizationmentioning
confidence: 47%
“…Transition metal coordination compounds with 3,5-dinitrobenzoate (DNB) have been widely studied and the ability of this ligand to coordinate in different modes involving the carboxylate and nitro groups has been recognized (Jassal et al, 2015;Hö kelek et al, 1998;Abdullah et al, 2010;Sinha et al, 2014;Miminoshvili et al, 2006). The use of a variety of coligands has resulted in structural and electronic modifications of DNB complexes that present multiple applications in fields such as magnetism, catalysis and photoluminescence (Valigura et al, 2017;Wang et al, 2013a;Paul et al, 2018;Lephoto et al, 2016;Dey et al, 2013). Mono-and polynuclear compounds of Mn II (Chen et al, 1995), Mn III (Paul et al, 2018;Song et al, 2010), Co II (Valigura et al, 2017;Wang et al, 2008Wang et al, , 2011Wang et al, , 2012Sarkar et al, 2010;Sharma et al, 2009;Xu & Xu, 2004;Betke et al, 2011;Qi, 2009;Pedireddi & Varughese, 2004;Qi et al, 2008;Zhang et al, 2010;Tahir et al, 1996;Yang et al, 2016;Roy, Oyarzabal et al, 2016), Co III (Sharma et al, 2007), Ni II (Zhang & Zhu, 2012;Wang, Hou et al, 2013;Chen et al, 2006;Zakaria et al, 2002;Hu et al, 2007) and Zn II (Lephoto et al, 2016;…”
Section: Introductionmentioning
confidence: 99%
“…The use of a variety of coligands has resulted in structural and electronic modifications of DNB complexes that present multiple applications in fields such as magnetism, catalysis and photoluminescence (Valigura et al, 2017;Wang et al, 2013a;Paul et al, 2018;Lephoto et al, 2016;Dey et al, 2013). Mono-and polynuclear compounds of Mn II (Chen et al, 1995), Mn III (Paul et al, 2018;Song et al, 2010), Co II (Valigura et al, 2017;Wang et al, 2008Wang et al, , 2011Wang et al, , 2012Sarkar et al, 2010;Sharma et al, 2009;Xu & Xu, 2004;Betke et al, 2011;Qi, 2009;Pedireddi & Varughese, 2004;Qi et al, 2008;Zhang et al, 2010;Tahir et al, 1996;Yang et al, 2016;Roy, Oyarzabal et al, 2016), Co III (Sharma et al, 2007), Ni II (Zhang & Zhu, 2012;Wang, Hou et al, 2013;Chen et al, 2006;Zakaria et al, 2002;Hu et al, 2007) and Zn II (Lephoto et al, 2016;Dey et al, 2013;Yin & Wang, 2005;Miminoshvili et al, 2003Miminoshvili et al, , 2004Jin et al, 2013;Wu et al, 2015; have been previously reported. Compounds with Cu II as the metal center have also been synthesized, such as five-coordinated Cu II complexes bearing bis(1,3-...…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards a number of tetrahedral Co(II) SIMs have been explored with varying relaxation barriers (14-230 cm −1 ) and axial ZFS parameter D (−5 to −160 cm −1 ) [23][24][25][26][27][28] where heavier donor atoms such as S, Se, P or I and the tight bite angles of the ligands enhance the magnetic anisotropy. In contrast to tetrahedral Co(II) SIMs, octahedral systems are rarely reported [29][30][31][32][33][34][35][36]. For distorted octahedral Co(II) ions the axial ZFS parameter D is expected to be positive owing to the easy plane (xy) of anisotropy [37] but in few cases it has been found to be negative [38], especially in mer-directing ligands where the octahedral geometry is distorted towards trigonal prismatic geometry [39].…”
Section: Introductionmentioning
confidence: 99%